Catalytic anodes and processes for use in electro-chlorination
A catalytic anode using cobalt oxide and antimony/tin oxides in a crystalline matrix addresses the high cost and inefficiency issues of noble metal-based anodes, enhancing chlorine evolution reactions and extending service life with improved electrical efficiency for water treatment systems.
Patent Information
- Application Number
- JP2024099007
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-23
AI Technical Summary
Existing electrochlorination systems face challenges with high costs due to the use of noble metals like iridium and ruthenium for catalytic anodes, which also suffer from inefficiencies such as competitive oxygen evolution reactions, durability issues, and acid corrosion, leading to reduced service life and increased maintenance costs.
A catalytic anode structure using a conductive metallurgical catalyst layer composed of cobalt oxide crystalline particles in a crystalline matrix of antimony and tin oxides, supplemented with limited noble metals, provides high selectivity and durability for chlorine evolution reactions, reducing the need for expensive noble metals and enhancing electrical efficiency.
The anode structure achieves high catalytic activity, selectivity, and durability with reduced overpotentials, extending service life and lowering operational costs while maintaining high electrical efficiency, suitable for industrial and municipal water treatment applications.
Smart Images

Figure 2025011036000003 
Figure 2025011036000004 
Figure 2025011036000005
Abstract
Description
[Technical field]
[0001] The present invention relates to catalytic anodes for use in electrochlorination systems for the production of chlorine from aqueous solutions containing chloride ions via a chlorine evolution reaction. Such chlorine generation systems are particularly useful in ballast water treatment systems and in the industrial treatment and purification of wastewater, such as industrial water. They can also be used in the industrial production of chlorine, particularly in the chlor-alkali process. [Background technology]
[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry that has found applications both in the large-scale generation of chlorine for capture and for immediate application. In the chlor-alkali process, chlorine and sodium hydroxide are produced by electrolysis of aqueous sodium chloride solution, and the products are recovered for further industrial use. Chlorine is an effective biocide, and therefore electrochlorination systems are used independently for water purification based on the in situ generation of aqueous chlorine and its immediate biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which has applications in various scenarios, such as industrial wastewater and general water disinfection. In addition, an increasing number of ships are being equipped with on-board ballast water treatment systems to treat ballast tank water before discharge. Ships traveling long distances may introduce invasive aquatic organisms into local ecosystems by discharging ballast water collected in remote areas. Invasive invasive species can have a significant impact on local ecosystem balance. Ship-mounted generator-powered electrochlorination systems provide an effective and immediate solution to treat such water before discharge. Effective industrial use of electrochlorination systems and methods relies on electrolysis cells that can operate efficiently for extended periods of time. To promote chlorine production at the anode, it is common in the art to apply a catalytic coating to the electrolyte-facing surface of the anode to catalyze the chlorine evolution reaction. Such catalytic coatings typically contain significant amounts of one or more precious metals, the most commonly used of which are iridium and ruthenium, which add significant cost and complexity to anode manufacture. There remains a continuing need in the art for new catalytic anodes that can more cost-effectively meet the various technical considerations associated with industrial or municipal electrochlorination environments. When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.
[0003] First, the catalyst selected must be sufficiently selective to the chlorine evolution reaction to reduce efficiency losses resulting from the competing oxygen evolution reaction, which may otherwise occur at the anode due to the electrolysis of water in aqueous solution. Second, the catalyst coating must be durable enough to withstand long-term operation and the acidification of the electrolyte that may occur during electrochlorination. Third, the anode coating should be highly conductive to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolysis cell. Indeed, it is clear that some overpotentials typically occur in electrolysis cells due to efficiency losses, but a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential over long-term operation provides a relevant indicator of electrode durability and service life. The physical durability of the catalytic coating on the anode can be evaluated both by its performance in long-term tests and, most preferably, by examining its morphology with a scanning electron microscope. In fact, catalytic anode coatings in the art typically exhibit an external surface morphology resembling a dry lake bed, with the appearance of finely sedimented deposits widely interrupted by characteristic "mud cracks", as shown in Figure 1. These cracks create weaknesses in the catalytic layer, allowing electrolyte and reactive species to penetrate toward the anode's substrate, weakening the bond between the catalyst and the substrate and resulting in a degradation process in which the exposed composition corrodes. Typically, this results in a loss of electrical efficiency (e.g., as manifested by an increase in overpotential) and a loss of catalytic activity, reducing the useful life of the anode and leading to expensive replacement. Summary of the Invention
[0004] The catalytic anode of the first aspect of the invention, obtainable by the method of the second aspect of the invention, offers an advantageous balance of properties that address the technical requirements of such an anode, while avoiding the need for expensive precious metals, particularly iridium. In particular, the catalytic coated anode structure defined in the first aspect of the invention exhibits high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of operational life, and improved resistance to acids formed during operation. The catalytic coated anode structure defined in the first aspect of the invention also has high anode conductivity, resulting in efficient electrical operation without excessive overpotentials, which is maintained over long periods of operation.
[0005] These advantages of the first aspect of the invention are provided by applying a conductive metallurgical catalytic layer to the electrolyte-facing surface of the anode, the catalytic layer comprising cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the chemical formula Co3O4 within a defined crystalline matrix of oxides of antimony and tin. The characteristic morphology and chemical composition of this metallurgical catalyst layer is best achieved by a preparation method employing control of reactants and process conditions as further defined in the second aspect of the present invention. The present invention therefore provides in a first aspect a catalytic anode structure for use in an electrochlorination system comprising an electrically conductive solid substrate overlaid on its electrolyte-facing surface with an electrically conductive metallurgical catalytic layer, the layer comprising cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the chemical formula Co3O4 within a crystalline matrix of oxides of antimony and tin, cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in the metallurgical catalyst layer is in the range of 2:1 to 9:1; A catalytic anode structure is provided.
[0006] In the anode of the first embodiment, the catalyst composition preferably further comprises one or more noble metals or oxide compounds thereof, and particularly preferably further comprises ruthenium or an oxide thereof. As used herein, the term "atomic % of the total metal atomic content" with respect to a particular metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, regardless of whether such metal element is present in elemental or compound form. As used herein, the term "overall metallic stoichiometric ratio" of a particular metallic element refers to the stoichiometric ratio of all atoms of such metallic element present in a composite metallurgical layer (or other composition, if applicable), regardless of whether such metallic element is present in elemental or compound form. For example, in a structure containing 15 atomic % antimony and 15 atomic % tin purely in elemental form, the overall metallic stoichiometric ratio of Sb:Sn is 15:15, i.e., 1:1, and in a structure containing 15 atomic % antimony in the form of elemental antimony, 15 atomic % elemental tin, and further compounded 15 atomic % tin in the form of an oxide, the overall metallic stoichiometric ratio of Sb:Sn is 15:(15+15), i.e., 1:2. In a preferred embodiment of the first aspect, the catalytic anode structure comprises a conductive solid substrate overlaid on its electrolyte-facing surface with a conductive metallurgical catalyst layer as defined above, in this embodiment the catalyst layer being directly adjacent to the substrate. In an alternative preferred embodiment of the first aspect, the catalytic anode structure comprises an electrically conductive solid substrate overlying a surface facing the electrolyte with a metallurgical interlayer and an electrically conductive metallurgical catalytic layer as defined above. In this alternative embodiment, the interlayer is directly adjacent to the substrate, and the catalytic composition overlies the interlayer to provide the catalytic surface layer. The preferred interlayer in this embodiment is a dimensionally stable anode composition, most preferably an interlayer composition as described herein below. The outer surface of the metallurgical catalyst layer of the above defined composition has the advantageous morphology of a continuous coating of agglomerated cobalt oxide particles embedded in a matrix of tin oxide and antimony oxide.
[0007] The term "morphology" is used herein to describe the three-dimensional structure and appearance of the material in question. Morphology can be most usefully determined by scanning electron microscopy, as described herein below, which provides a three-dimensional image of the surface of the material so as to allow direct visual appreciation of its structure and appearance. Also, within this specification, the term "continuous coating" is used to describe a coating that completely covers the underlying electrode material. Preferably, this continuous coating is not interrupted by significant cracks or other through discontinuities that weaken its integrity. In particular, the continuous coating of the metallurgical catalyst layer of the present invention advantageously does not exhibit the extensive "mud crack" precipitate morphology of conventional catalyst coatings used in electrochlorination, but instead provides a continuous surface coating or layer composed of a three-dimensional matrix of agglomerated particles as viewed under a scanning electron microscope. The present invention is based in part on the discovery that a catalyst composition essentially based on cobalt oxide advantageously provides an anode structure with excellent properties for obtaining a CER reaction in electrochlorination. The resulting metallurgical catalyst layer on the anode provides the anode with excellent durability in terms of operating life and provides advantageous catalytic activity and selectivity for the chlorine evolution reaction. The metallurgical catalyst layer also provides the anode with high resistance to acid corrosion and high conductivity, which translates into high electrical efficiency and long-term operating performance at low overpotentials. The use of a catalyst composition based mainly on cobalt oxide instead of a larger amount of precious metal also makes it possible to achieve this anode performance at a significantly lower cost than conventional catalytic anodes based mainly on iridium and / or ruthenium.
[0008] In particular, the cobalt oxide crystalline particles serve as the essential catalytic species of the metallurgical catalyst layer, providing highly selective catalysis for the CER reaction at a cost significantly lower than precious metal-based catalyst compositions such as iridium-based compositions. Although the essential cobalt oxide catalyst of the present invention may be supplemented with catalytic precious metal oxides, cobalt should be present in an amount of at least 12.5 atomic % of the total metal atom content of the metallurgical catalyst layer, and thus is the predominant catalytic species in the catalyst composition. This use of cobalt oxide as the predominant catalytic species is made possible by the use of a defined antimony and tin oxide matrix in the catalyst layer in combination therewith, which combination serves to provide a highly selective, durable, and efficient cobalt oxide-based catalytic anode for CER with the improved balance of properties described above.
[0009] The agglomerated crystalline particles on the outer surface of the metallurgical catalyst layer are also essential to provide a highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transport limitations of conventional lake bed precipitated catalyst layers, allowing the catalytic anode of the first aspect of the invention to operate at higher efficiency for the chlorine evolution reaction, contributing to various advantages of the invention. The efficiency advantage of the catalytic anode of the present invention in the chlorine evolution reaction is particularly exhibited by aqueous solutions of chloride ions having low salt levels (e.g., brine). The improved efficiency at low salt levels makes the electrode more suitable for a wide range of water treatment applications, such as municipal water applications or drinking water treatment, in addition to wastewater treatment and other chlorination applications. The improved efficiency also results in reduced levels of unwanted electrolysis by-products, such as chlorate and perchlorate ions. In a preferred form of the catalytic anode of the first aspect, the catalytic composition does not contain titanium or compounds thereof. Such titanium-free catalytic composition provides the resulting anode with the additional advantage of being highly suitable for use in current reversal cells. Current reversal has become an easy-to-maintain means of removing deposits of metals such as calcium and magnesium that may otherwise accumulate on the cathode during long-term electrolysis operation, especially for treating municipal or residential water, such as pools with low salt levels. However, conventionally, current reversal inside a cell causes more rapid deterioration and damage to the anode catalytic coating, since significant pH fluctuations occur at the surface of the electrode, especially within the crack surfaces of the "mud crack" catalyst, and electrolyte may become saltwater depleted, thus allowing competing water splitting reactions to occur more widely. Titanium present in the coating is easily dissolved in this environment, leading to weakening of the catalytic coating on the substrate and rapid deterioration of the coating and performance. The present invention provides an anode that can eliminate the presence of titanium in the catalytic composition due to the high efficiency of the catalytic composition and the inclusion of cobalt oxide, thereby avoiding this deterioration and resulting in a longer anode life, especially in current reversal environments.
[0010] Such titanium-free catalyst compositions also provide the resulting anode with the added advantage of greater resilience in the high salt level chlor-alkali process. Typically, chlor-alkali cells are characterized by a Teflon or similar membrane disposed between the cathode and anode. Caustic solutions inside the cell can cause the membrane to perforate, allowing the caustic solution to reach the anode, causing corrosion and depletion of titanium. The present invention provides an anode that is highly efficient and, due to the inclusion of cobalt oxide, can eliminate the presence of titanium in the catalyst composition, thereby avoiding this degradation and resulting in longer anode life in this environment. Formation of the catalytic anode structure of the first aspect of the present invention is best achieved by a process of adding catalyst composition under process conditions ideally favorable to forming a catalyst layer of the correct composition on the anode surface and resulting in a metallurgical catalyst layer of the desired morphology.
[0011] The present invention therefore provides in a second aspect a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical catalyst precursor composition, the composition comprising cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the formula Co3O4 dispersed in a mixture of compounds of antimony and tin, the cobalt oxide being present in an amount of at least 12.5 atomic % of the total metal atomic content of the composition, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in the composition is within the range of 20:80 to 80:20. Includes the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0012] The process of the second aspect is particularly characterized by the use of particular starting metallurgical compositions and preparation conditions that result in the anode structure of the first aspect. In a preferred embodiment of the second aspect, the method comprises steps (a) and (b) and leads to a catalytic anode structure consisting of a conductive solid substrate overlaid on its electrolyte-facing surface with a conductive metallurgical catalytic layer as defined above, in this embodiment the catalytic layer is directly adjacent to the substrate. In an alternative embodiment of the second aspect, between method steps (a) and (b), an additional metallurgical composition (c) can be applied, leading to a catalytic anode structure comprising a conductive solid substrate overlying on its electrolyte-facing surface a metallurgical interlayer (derived from the additional metallurgical composition (c)) and a conductive metallurgical catalytic layer as defined above. In this alternative embodiment, the interlayer is directly adjacent to the substrate and the catalytic composition overlies the interlayer to provide a catalytic surface layer. The application of the specified process solvent during application step (b), as well as the subsequent drying and heat treatment of the resulting structure, contributes to the formation of advantageous morphology and composition of the resulting metallurgical catalytic layer on the anode of the present invention.
[0013] Importantly, it has been found that final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical catalyst layer, in particular by promoting high selectivity for the chlorine evolution reaction over the oxygen evolution reaction via water splitting. In this regard, in the second aspect of the invention, a final heat treatment in the range of 450-550°C, and in particular an optimum final heat treatment at 500°C, is preferred, where higher selectivity for the chlorine evolution reaction and durability are observed. In the second aspect of the invention, the use of a specified process solvent for applying the metallurgical composition in step (b) is also essential, the process solvent being a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. It has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents in terms of the dissolving power of the starting compounds used in the method of the second aspect. In addition, it has been found that this composition of the process solvent is advantageous for the control of the surface morphology of the layer formed by the application of the metallurgical composition, both before and after the final heat treatment step, and in particular contributes to an agglomerated particulate morphology free of integrity weakening cracks. This ability to control the layer morphology is particularly due to the choice of alcohol and the alcohol to water ratio in the process solvent, with control being optimal at a ratio of 85:15 (isopropanol:water).
[0014] In a preferred embodiment of the present method, it has been found that applying the metallurgical catalyst precursor composition to a substrate that is heated to a specified temperature range of 55-200° C. during the application step, and preferably throughout the entire application step, enhances the formation of the desired metallurgical catalyst layer on the anode. Importantly, it has also been found that drying the resulting structure within the same temperature range of 55-200°C enhances the formation of the desired metallurgical catalyst layer, particularly by promoting the formation of the desired morphology of a continuous layer uninterrupted by mud cracks or other significant through-hole discontinuities.
[0015] Further aspects of the invention are also described herein below, An electrochlorination system comprising an electrolytic anode structure obtainable by the method of the first or second embodiment, and An electrolytic process for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the process of the first aspect or of the second aspect, at the anode chlorine gas is generated from the aqueous solution. Includes. In a preferred embodiment of the electrolysis process, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly to disinfect ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for the production and recovery of chlorine. The invention will now be described in more detail as follows. This application includes the following figures: [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 illustrates a lake bed morphology of a conventional catalyst bed having extensive "mud cracks." [Diagram 2] FIG. 2 illustrates the aggregate particulate morphology of an embodiment of the present invention. [Diagram 3] FIG. 1 illustrates the anode life improvement by combining defined stoichiometric amounts of cobalt, tin, and antimony in the catalyst precursor composition of the present method. [Figure 4] FIG. 1 illustrates the anode life improvement by combining defined stoichiometric amounts of cobalt, tin, and antimony in the catalyst precursor composition of the present method. [Diagram 5] FIG. 1 shows the anode CER efficiency improvement by including defined stoichiometric amounts of tin and antimony in the catalyst precursor composition of the present method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] First aspect of the present invention (catalytic anode) The catalytic anode structure of a first embodiment comprises an electrically conductive solid substrate having overlying on its electrolyte-facing surface an electrically conductive metallurgical catalyst layer, the layer comprising cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the chemical formula Co3O4 within a crystalline matrix of oxides of antimony and tin, the cobalt oxide being present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in the metallurgical catalyst layer is in the range of 2:1 to 9:1. The anode structure of the first aspect of the invention is obtainable, and preferably obtainable, by the method of the second aspect of the invention. The anode structure of the first embodiment, particularly when prepared according to the method of the second embodiment, advantageously has the property that the outer surface of the metallurgical catalyst layer has the morphology of a continuous coating of agglomerated particles. The presence of occasional cracks or other surface discontinuities or fault lines is not excluded so long as such imperfections do not penetrate to the depth of the catalyst layer composition or expose the underlying substrate to electrolytic corrosion. Preferably, however, the anode structure of the first embodiment has a metallurgical catalyst layer having an outer surface morphology of a continuous, crack-free coating of agglomerated particles. The advantageous agglomerated particulate morphology of the outer surface of the metallurgical catalyst layer contrasts with the widespread crack-precipitate-like surface morphology of conventional catalytic anodes and can be best visualized by examination under a scanning electron microscope, as shown in the accompanying figures. In each case, the electron micrographs were obtained using a JSM-IT500 InTouchScope™ scanning electron microscope instrument, using the settings described in the associated figure legend. In Figure 1, scanning electron microscopy of the exterior surface morphology of a conventional catalytic anode for electrochlorination reveals a characteristic "mud-crack" appearance with extensive deep cracks extending throughout the deposit-like surface coating. Such a morphology renders the catalytic surface susceptible to chemical attack, weakening its structural integrity and reducing its life and usefulness. In contrast, in FIG. 2, scanning electron microscopy, at the indicated magnification, shows the surface of a preferred catalytic anode of the first embodiment having a continuous, crack-free surface layer and an aggregated particulate morphology.
[0018] An essential element of the anode structure of the first embodiment is the presence of cobalt oxide present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalyst layer. The anode of the present invention provides excellent durability in terms of the operating life of the catalyst on the anode substrate, high resistance to acid corrosion, and high conductivity, and provides a means to apply to the anode high levels of cobalt oxide-based catalyst in a form that is highly selective for electrochlorination, leading to high electrical efficiency and low overpotential operating performance. The use of a catalyst composition based primarily on cobalt oxide instead of precious metals as the primary catalytic component can also make it possible to obtain this anode performance at a significantly lower cost than conventional precious metal-based catalysts such as iridium-based catalytic anodes. Preferably, in the anode structure of the first aspect, cobalt oxide is present in the highest amount practical to maximize its catalytic effect while still obtaining other advantages of the invention. Accordingly, it is preferred that cobalt is present in an amount of at least 15 atomic % of the total metal atomic content of the metallurgical catalyst layer, more preferably at least 20 atomic % of the total metal atomic content of the metallurgical catalyst layer. Even more preferably, cobalt is present in an amount of at least 30 atomic % of the total metal atomic content of the metallurgical catalyst layer, most preferably at least 40 atomic % of the total metal atomic content of the metallurgical catalyst layer. Ideally, cobalt is present in an amount of 50-80 atomic % of the total metal atomic content of the metallurgical catalyst layer, optionally within the range of 60-75 atomic % of the total metal atomic content of the metallurgical catalyst layer. Such a cobalt content is advantageously achieved by preparing the anode structure according to the method of the second aspect of the invention.
[0019] The individual metal contents and total metal stoichiometry of the metallurgical catalyst layer can be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectroscopy) to determine the compositional characteristics of the present invention. In the anode structure of the first embodiment, the cobalt oxide crystalline particles in the catalyst composition preferably consist of crystalline cobalt oxide having the formula Co3O4. The presence of this crystalline form of cobalt oxide can be confirmed by X-ray diffraction or other conventional crystallographic techniques. The Co3O4 crystalline particles can be sized by directly measuring their diameter in transmission electron micrograph images, and the diameter is preferably in the range of 1 nm to 20 nm, more preferably 1 nm to 10 nm, and most preferably 3 nm to 7 nm. In the anode of the first embodiment, the catalyst composition preferably further comprises one or more precious metals or oxide compounds thereof, and more preferably further comprises ruthenium or an oxide thereof. For the purposes of the present invention, the amount of any included precious metal should be small enough so as not to reduce the cobalt content of the metallurgical catalyst layer below the level defined by the present invention, and preferably the amount of precious metal should not exceed 10 atomic %, more preferably not exceed 5 atomic %, of the total metal atomic content of the metallurgical catalyst layer.
[0020] In a more preferred embodiment, the cobalt oxide crystalline particles in the catalyst composition consist essentially of crystalline cobalt oxide having the formula Co3O4 and further consist essentially of ruthenium at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particles, at least a portion of said ruthenium being present on the crystalline particles in the form of a surface decoration. In this latter embodiment of the anode, the cobalt oxide crystalline particles in the catalyst composition, in addition to the surface decoration, may further include crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide, or forms a mixed metal oxide with cobalt, or both. In such embodiments, the limited amount of ruthenium provided in the catalyst composition associated with the cobalt oxide crystalline particles provides the advantage of further improving the properties of the metallurgical catalyst layer on the anode, most notably improving the selectivity of the catalyst for the chlorine evolution reaction and improving the durability of the anode, especially in terms of operating life. The ruthenium may be present in the form of an oxide compound or in the form of a metallic element, at least when incorporated within the crystal lattice of the cobalt oxide. In such embodiments, the ruthenium associated with the cobalt oxide catalyst may be present in a total non-stoichiometric proportion approaching a mixture of elemental ruthenium and oxide-bound ruthenium.
[0021] However, it has been found that if the ruthenium content in the crystalline particles of the catalyst composition exceeds the upper limit of 5 atomic %, it leads to a decrease in the efficiency of the chlorine evolution reaction, as manifested by a decrease in the low salt efficiency, particularly in the case of water treatment applications.For this reason, the ruthenium content associated with the cobalt oxide catalyst particles should be limited to the levels described, and it is not advantageous to further increase the ruthenium content in the hope of any further improvement. In all the above embodiments of the anode of the first aspect, the metallurgical catalyst layer comprises cobalt oxide crystalline particles distributed on the upper surface of the anode structure. The catalyst composition consists essentially of cobalt oxide crystalline particles distributed within a crystalline matrix of antimony oxide and tin oxide, the matrix preferably being free of substantial or any amount of precious metal oxides such as palladium or iridium other than those provided herein for the invention. In particular, in all embodiments of the anode, the catalyst composition consists essentially of cobalt oxide crystalline particles in a crystalline matrix of antimony and tin oxides, which catalyst composition is present on the electrolyte-facing surface of the anode. Surprisingly, it has been found that the total ratio of cobalt:antimony and tin combined in the metallurgical catalyst layer provides advantageous performance. By maintaining this ratio within the specified range, the durability of the catalytic anode is improved, as evidenced by an increase in useful operating life. This increase in life provides highly advantageous performance to the anode of the first embodiment.
[0022] In particular, in all embodiments of the anode, the catalytic composition comprises, and preferably consists essentially of, cobalt oxide crystalline particles in a crystalline matrix of antimony and tin oxides. The total metal stoichiometric ratio of cobalt:total antimony and tin in the metallurgical catalytic layer is preferably in the range of 2:1 to 9:1. More preferably, the total metal stoichiometric ratio of cobalt:total antimony and tin in the metallurgical catalytic layer is in the range of 2.5:1 to 6:1, and most preferably in the range of 3:1 to 5:1. Optimally, the metallurgical catalytic layer is in the range of 3:1 to 4:1. Surprisingly, it has been found that the total metal stoichiometric ratio of cobalt:total antimony and tin in the metallurgical catalytic layer provides advantageous performance. By maintaining this ratio within the basic ranges described above, the durability of the catalytic anode is improved, which is manifested by an increase in useful operating life. This increase in life provides highly advantageous performance to the anode of the first aspect. In the anode, the antimony and tin compounds serving as a matrix in the catalyst composition are preferably present in an amount that provides the metallurgical catalyst layer with a total metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:100. In this regard, it has been surprisingly further found that the total metal stoichiometry of antimony:tin in the metallurgical catalyst layer provides an additional contribution to obtaining optimal anode performance. Maintaining this total stoichiometry within the above range provides the anode with a further improved operating life and also improves the CER efficiency of the cell, as evidenced by the faradaic efficiency.
[0023] The antimony and tin compounds are preferably present in the metallurgical catalyst layer in an amount that provides a preferred overall stoichiometric ratio of antimony:tin in the range of 1:25 to 1:100, most preferably in the range of 1:50 to 1:84. Optimally, this ratio may be in the range of 1:50 to 1:85, and in superior embodiments, 1:75 and 1:84. In each of the above embodiments of the anode structure, the metallurgical catalyst layer preferably further comprises at least one palladium compound in an amount to provide the layer with a total palladium content of up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. The introduction of limited amounts of palladium into the composite layer is preferably achieved by including one or more palladium-based compounds in the catalyst composition or by subsequent doping. Palladium provides a further improvement in chlorine evolution reaction efficiency, particularly for water treatment applications, as evidenced by an increased low salt efficiency. However, when the palladium content in the catalyst composition exceeds the upper limit of 7 atomic %, no further improvement in the efficiency of the chlorine generation reaction is achieved, as evidenced by no further increase in the low salt efficiency, particularly in the case of water treatment applications. For this reason, the palladium content associated with the cobalt oxide catalyst particles should be limited to the levels described in order to avoid unnecessary cost and complexity. It is preferred that the total palladium content is at most 5 atomic % of the total metal atomic content of the composite metallurgical layer, more preferably at most 3 atomic %, and optimally, the total palladium content is at most 1.5% of the total metal atomic content of the composite metallurgical layer.
[0024] The anode of all embodiments of the first aspect essentially consists of a conductive solid substrate, which substrate is known in the art. This substrate preferably essentially consists of valve metals such as titanium, zirconium, niobium, and tantalum (and alloys / mixtures containing these metals), and preferably titanium, most preferably titanium. Mixtures of valve metals may also be present in the substrate. Oxides of one or more valve metals essentially present in the substrate may be further observed or produced as artifacts under the conditions of anode manufacture and use, especially at the surface of the substrate or at the interface with the metallurgical catalyst layer, and their presence is not excluded from the substrate of the present invention, unless they form the main component of the substrate. Anode substrates can be produced by conventional means in the art, purchased or custom manufactured, and formed into any shape suitable for end use as an anode in an electrochemical cell or system. In particular, substrates can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Substrates may be coated on one or more sides with complex metallurgical layers depending on their design and configuration.
[0025] In the anode of all embodiments of the first aspect, the distribution of the cobalt oxide-based catalytic composition is spread throughout the depth of the metallurgical catalyst layer. The distribution of the metal elements throughout the thickness of the structure of the metallurgical catalyst layer according to the present invention can be visualized by imaging using a transmission electron microscope (TEM) according to the mapping technique TEM-EDS (Transmission Electron Microscopy and Energy Dispersive X-ray Analysis). Using TEM-EDS techniques, it is possible to directly image the distribution of the various essential constituent metals and observe their distribution within the thickness of the metallurgical catalyst layer, and to confirm the presence of the anode structure of the present invention, especially when compared with the overall image obtained by HAADF (High Angle Annular Dark Field Transmission Electron Microscopy). Using TEM-EDS mapping techniques, it is possible to visualize each metal element individually within the metallurgical catalyst layer. In particular, it is easily observed that the cobalt of the cobalt oxide particles is present in a high density concentration (coating) on the outer surface of this layer, but it is further evident that the cobalt is present in a lower density throughout the depth of this layer. Thus, ruthenium, which is present at low levels in the catalyst composition, appears in a lower density in the surface regions where the cobalt catalyst density is higher, according to TEM-EDS. Tin is distributed throughout this layer and is present in the antimony-tin matrix of the catalyst composition.
[0026] The distribution and concentration of metal elements throughout the metallurgical catalyst layer can also be quantitatively measured using TOF-SIMS (Time of Flight Secondary Ion Mass Spectroscopy) technique, which allows mapping of metal concentrations throughout the depth of the metallurgical catalyst layer and can also confirm the presence of the structures of the present invention. In the anode of the first embodiment, the cobalt of the catalyst composition is preferably distributed throughout the thickness of the metallurgical catalyst layer. In a further enhanced embodiment of the anode of the first aspect, the metallurgical catalyst layer further comprises ruthenium oxide distributed throughout or substantially throughout the catalyst layer. In particular, the ruthenium oxide is preferably distributed within a catalytic matrix of antimony oxide and tin oxide as described herein above. The inclusion of ruthenium oxide throughout or substantially throughout the metallurgical catalyst layer further improves the electrical conductivity of the layer, increasing the low salt efficiency of the anode and improving the long term durability of the anode structure.
[0027] In a further preferred embodiment of the anode of the first aspect, an additional metallurgical layer (the "interlayer") may be present directly on the anode substrate to provide a base layer for an upper layer catalyst composition. In one preferred interlayer embodiment, ruthenium oxide may be advantageously applied as an intermediate layer (or "interlayer") between the anode substrate and the catalyst composition, preferably during the method of the second aspect, and subsequent heat treatment of the resulting structure leads to migration of the ruthenium oxide interlayer throughout the catalyst layer, providing enhanced conductive pathways through the catalyst layer, as well as other advantages identified above. In another preferred interlayer embodiment, the interlayer composition may comprise a mixture of metal oxides, preferably known in the art as a dimensionally stable anode composition. Such a mixture may comprise titanium oxide, tin oxide, and / or ruthenium oxide, and may form a separate interlayer between the anode substrate and the metallurgical catalyst composition, and function as a structural base composition rather than a traditional catalyst layer.
[0028] In a more preferred form of the above intermediate layer embodiment, the intermediate layer of the anode structure comprises titanium or one or more compounds thereof, or tantalum or one or more compounds thereof, or both. Such intermediate layer provides a protective layer on the anode substrate, onto which the metallurgical catalyst composition of the present invention is then applied. Optionally, an intermediate layer of ruthenium oxide may be applied between the intermediate layer comprising titanium and / or tantalum on the substrate and the metallurgical catalyst composition forming the outer layer of the anode structure. In an alternative preferred embodiment, the anode has a single intermediate layer comprising ruthenium or one or more compounds thereof, and preferably also titanium or one or more compounds thereof. Such an intermediate layer eliminates the need for a separate intermediate layer of ruthenium or a ruthenium compound, and instead includes ruthenium or a ruthenium compound within the intermediate layer structure beneath the metallurgical catalyst composition that forms the outer layer of the anode structure.
[0029] In another alternative embodiment, the anode structure interlayer comprises iridium or one or more compounds thereof in a limited amount such that the level of iridium does not prevent the fulfillment of the overall objectives of the present invention. Thus, the anode structure comprises iridium in the form of its oxide or other catalytically active species in an amount that provides a total iridium content of up to 15 atomic %, preferably up to 5 atomic %, of the total metal atomic content of the metallurgical catalyst layer. Iridium may be present in addition to other interlayer metallurgies as defined above, most notably ruthenium, or titanium or tantalum, or mixtures thereof. In the above interlayer anode structures, the titanium, tantalum, ruthenium or iridium compounds, when present, preferably comprise, and preferably consist of, oxide compounds. Alternatively, the interlayer composition may comprise a mixture of metal oxides that migrate to or intermingle with the top layer catalyst composition, thereby forming a composite metallurgical layer on the electrolyte-facing surface of the anode. Preferably, the defined base composition comprising ruthenium, tin and / or titanium oxides is additionally present as a structural base layer for the overlayer catalyst composition, thereby providing structural integrity to support the overlayer cobalt-based catalyst composition.
[0030] A preferred embodiment of the structural base composition of this alternative intermediate layer embodiment of the anode of the first aspect comprises, and preferably consists essentially of, metal oxide compounds of ruthenium, tin and titanium. The combination of these three metals is important to obtain the ideal morphology of the structural base composition in situ on the anode surface. Other metal oxides or other compounds may also be present as long as they do not adversely affect the morphology of the base composition, but most preferably the structural base composition consists of metal oxide compounds of ruthenium, tin and titanium. In particular, the particular combination of ruthenium, tin, and titanium provides a base structure composition that exhibits a base morphology of agglomerated particles interspersed with voids, resulting in a crack-free base structure that provides a resilient base structure onto which the catalyst composition can be applied. Furthermore, the particular combination of ruthenium, tin, and titanium in the structural base composition provides improved durability of the anode of the first aspect of the invention as compared to a similar base composition containing only ruthenium and titanium, or only ruthenium and tin. In this regard, the combination of both tin and titanium with ruthenium provides the anode of the invention with improved anode life and improved mechanical adhesion, further contributing to the benefits of the invention.
[0031] The above-described embodiments of the first aspect of the invention may, in addition to the above-described features, include one or more further components to enhance certain properties of the anode, so long as the overall advantages of the invention are still obtained. For example, in the anode structure of any preceding embodiment, the catalyst composition may further include a precious catalytic metal (in addition to any palladium, if present), preferably iridium, in the form of its oxide or other catalytically active species, in an amount to provide a total additional precious metal content, preferably an iridium content, of up to 15 atomic %, preferably up to 5 atomic %, of the total metal atomic content of the composition. This optional presence of small amounts of precious metal, particularly iridium, may be preferable in terms of further enhancing the catalytic performance of the anode, but should be limited according to the objective of the invention to minimize the use of expensive precious metals and rely mainly on cobalt oxide for catalytic activity. Thus, the amount of such precious metal is much less than that typically used when the catalyst composition is based on such metal. Alternatively or additionally, the catalyst composition on the anode of all embodiments may further comprise at least one copper compound in an amount to provide the catalyst composition with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, of the total metal atomic content of the metallurgical catalyst layer; or at least one aluminum compound in an amount to provide the catalyst composition with a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, of the total metal atomic content of the metallurgical catalyst layer; or at least one nickel compound in an amount to provide the layer with a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, of the total metal atomic content of the metallurgical catalyst layer; or more than one of the above. The further presence of copper or aluminum or nickel in the catalyst composition provides a further increase in catalyst selectivity for the chlorine evolution reaction, for example as measured by low salt efficiency. It is preferred that copper and / or aluminum and / or nickel are introduced via the catalyst composition and are preferably present in the catalyst composition in the form of one or more oxide compounds.
[0032] Second aspect of the present invention (preparation method) A second aspect is a method for preparing a catalytic anode structure for use in an electrochlorination system, comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) applying directly to the electrolyte-facing surface of the substrate an electrically conductive metallurgical catalyst precursor composition, the composition comprising cobalt oxide crystalline particles consisting essentially of crystalline cobalt oxide having the formula Co3O4 dispersed in a mixture of compounds of antimony and tin, the cobalt oxide being present in an amount of at least 12.5 atomic % of the total metal atomic content of the composition, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in the composition is within the range of 20:80 to 80:20. Including, the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450 ° C. A method is provided.
[0033] The method of the second aspect of the invention results in a catalytic anode structure as defined in the first aspect of the invention and is a preferred method for preparing the anode of the first aspect. In a first preferred embodiment of the method, in step (b), the metallurgical catalyst precursor composition is applied directly to the electrolyte-facing surface of the substrate to provide an anode, with the metallurgical catalyst composition directly adjacent to the substrate. In a second preferred embodiment of the method, prior to step (b), a metallurgical base composition is applied directly to the electrolyte-facing surface of the substrate to form a metallurgical interlayer immediately adjacent the substrate surface, and in step (b), a metallurgical catalyst precursor composition is applied to an outer surface of the metallurgical interlayer. In this embodiment, the metallurgical interlayer is preferably a dimensionally stable anode composition, and more preferably is one or more interlayers of the preferred types described above in relation to the first aspect of the invention. The temperature conditions and process solvents defined in the method of the second embodiment are important to obtain the desired catalytic anode structure. In the present method, after drying, the resulting dried structure is heat treated at a temperature in the range of at least 450° C., preferably in the range of 450-550° C. More preferably, the resulting dried structure is heat treated at a temperature in the range of 475-525° C., optimally at a temperature of 500° C. The method of the present invention also requires the use of a specific process solvent for applying the metallurgical composition in step (b), which is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5, preferably in a volume ratio range of 82.5:17.5 to 87.5:12.5. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15.
[0034] This composition of process solvent has been found to exhibit advantages over similar alcoholic solvents in terms of dissolving power for the starting compounds used in the method of the second aspect. In addition, this composition of the process solvent has been found to be advantageous for controlling the surface morphology of the layer formed by application of the metallurgical composition, both before and after the final heat treatment step, and in particular contributes to obtaining a cohesive particulate morphology free of integrity-weakening cracks. This ability to control the layer morphology is due in particular to the choice of alcohol and the alcohol to water ratio in the process solvent, with control being optimal at a ratio of 85:15 (isopropanol:water). Preferably, in the method of the present invention, the anode substrate (a) is heated during step (b) to a temperature in the range of 55-200°C, and the resulting structure is then dried at a temperature within the same range. Preferably, heating of the anode substrate to this temperature range is carried out throughout step (b), and the resulting structure is then dried at a temperature within the same range. Optimally, the substrate (a) is heated to a temperature of 100°C throughout step (b), and the resulting structure is then dried at that temperature.
[0035] In addition, the same heat treatment and specified process solvent may be used to apply the metallurgical-based composition as in the second embodiment involving the formation of an intermediate layer prior to step (b) of the method. The specified conditions and specified process solvent for heating the substrate during application step (b), as well as the subsequent drying and heat treatment of the resulting structure, contribute to the formation of the advantageous morphology and composition of the resulting composite metallurgical layer on the anode of the present invention. In particular, it has been found that applying the catalyst composition to a substrate that has been heated in accordance with the second aspect of the invention enhances the formation of the desired metallurgical catalytic layer on the anode. Importantly, it has also been found that drying the resulting structure within the same temperature range enhances the formation of the desired metallurgical catalytic layer, particularly because it promotes the formation of the desired morphology of a continuous layer uninterrupted by mud cracks or other significant through discontinuities. Importantly, it has also been found that final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical catalyst layer by promoting higher selectivity for the chlorine evolution reaction over the oxygen evolution reaction from water splitting. In this regard, in the second aspect of the invention, a final heat treatment in the range of 450-550°C, and in particular an optimum final heat treatment at 500°C, is preferred, where higher selectivity for the chlorine evolution reaction and mechanical adhesion are observed. In the method of the second aspect, the use of the temperature conditions and process solvents defined above in combination with the defined metallurgical content of the starting composition results in the formation of a metallurgical catalyst layer on the anode substrate having a desired composition and morphology suitable for use as an anode of the first aspect.
[0036] In the method of the second embodiment, the electrically conductive metallurgical catalyst precursor composition comprises cobalt oxide crystalline particles of the type described hereinabove with respect to the first embodiment. In this regard, the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of crystalline cobalt oxide having the chemical formula Co3O4. In one such embodiment, such cobalt oxide crystalline particles may consist of crystalline cobalt oxide having the chemical formula Co3O4. The presence of this crystalline form of cobalt oxide may be confirmed by x-ray diffraction or other conventional crystallographic techniques. In another more preferred embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition consist essentially of crystalline cobalt oxide having the formula Co3O4 and further consist essentially of ruthenium at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particle, at least a portion of said ruthenium being present on the crystalline particle in the form of a surface decoration. In this latter embodiment, the cobalt oxide crystalline particles in the catalyst precursor composition, in addition to the surface decoration, may further include crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide, or forms a mixed metal oxide with cobalt, or both.
[0037] The limited amount of ruthenium provided in association with the cobalt oxide crystalline particles in the catalyst precursor composition in such embodiments provides the advantage that when applied to the anode in the method of the present invention, it further improves the properties of the metallurgical catalyst layer, most notably by improving the selectivity of the catalyst for the chlorine evolution reaction and improving the durability of the anode, particularly in terms of operating life. The ruthenium may be present in the form of an oxide compound or may be present in the form of a metallic element, at least when incorporated within the crystal lattice of the cobalt oxide. In such embodiments, the ruthenium associated with the cobalt oxide catalyst may be present in a total non-stoichiometric proportion approximating a mixture of elemental ruthenium and oxide-bound ruthenium. However, it has been found that exceeding the upper limit of 5% of the ruthenium content associated with the crystalline particles in the catalyst precursor composition leads to a decrease in the efficiency of the chlorine evolution reaction, as manifested by a decrease in the low salt efficiency, particularly in the case of water treatment applications.For this reason, the ruthenium content associated with the cobalt oxide catalyst particles should be limited to the levels described, and there is no advantage to further increasing the ruthenium content in the hope of any further improvement. In all the above embodiments, the catalyst precursor composition consists essentially of cobalt oxide crystalline particles dispersed in a mixture with other metal compounds, including antimony and tin, which, when applied by the method of the second aspect, will result in a crystalline matrix of metal oxides of antimony and tin in the final catalyst composition of the anode of the invention. It is particularly preferred that such other metal compounds do not substantially or in any amount contain precious metal oxides such as palladium or iridium other than those defined herein for the present invention.
[0038] In this regard, the method of the second aspect is advantageously carried out using as a catalyst precursor a composition in which cobalt oxide crystalline particles (as described above) are dispersed in a mixture of antimony and tin compounds, the total metal stoichiometry of cobalt:antimony and tin combined in the composition being within the range of 20:80 to 80:20. This combination of antimony and tin compounds in the composition, when applied by the method of the second aspect, results in a crystalline matrix of antimony oxide and tin oxide in which the crystalline particles of cobalt oxide aggregate to give rise to the desired morphology of the metallurgical catalyst layer. In this preferred embodiment, it has also been found that the use of a molar ratio of cobalt:antimony and tin combined within the ranges specified for the metallurgical catalyst precursor composition provides increased operational durability of the anode structure resulting from the method of the present invention as indicated by maintaining a lower overpotential for a longer period of time as compared to ratios outside the specified ratio ranges. Additionally, being within the specified ratio ranges increases the efficiency of the resulting catalytic anode for the chlorine evolution reaction. In this regard, the total metal stoichiometric ratio of cobalt:antimony and tin combined is preferably between 30:70 and 80:20, more preferably between 60:40 and 40:60, with a ratio of 50:50 being most preferred and optimal for obtaining a resulting anode having a high CER efficiency and a longer operational life with low overpotential.
[0039] In the preferred embodiment above, it has also been found that by using a metallurgical catalyst precursor composition in which the total metal stoichiometry of the sum of cobalt:antimony and tin is controlled as described above, and further in which antimony and tin compounds are present in the composition in amounts to provide a total metal stoichiometry of antimony:tin of up to 1:10, preferably up to 1:20, the performance of the resulting anode can be further enhanced when prepared according to the method of the second aspect. Additionally, by controlling the ratio of antimony to tin in the composition within this range, the method of the present invention provides an anode with further improved efficiency in the chlorine evolution reaction. More preferably, in this highly advantageous embodiment of the method, the total metal stoichiometry of antimony:tin in the metallurgical catalyst precursor composition is at most 1:50, in particular at most 1:100. The optimal total metal stoichiometry of antimony:tin in composition (iii) for achieving increased efficiency of the chlorine evolution reaction is 1:200. Most preferably, the metallurgical catalyst precursor composition combines the preferred range of the sum of cobalt:antimony and tin ratios with the preferred range of antimony:tin total metal stoichiometric ratios. Such compositions serve as particularly effective metallurgical catalyst precursor compositions in the process of the second aspect of the invention, leading to the formation of anode structures having a particularly effective combination of efficiency in the chlorine evolution reaction and high durability providing longer operating life at low overpotentials.
[0040] Thus, particularly in the method of the second aspect, it is preferred that the metallurgical catalyst precursor composition comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, the total metal stoichiometric ratio of cobalt:antimony and tin combined being in the range of 20:80 to 80:20, and the total metal stoichiometric ratio of antimony:tin being at most 1:10, preferably at most 1:20. It is more preferred that the metallurgical catalyst precursor composition comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, the total metal stoichiometric ratio of cobalt:antimony and tin combined being in the range of 40:60 to 60:40, and the total metal stoichiometric ratio of antimony:tin being at most 1:50, preferably at most 1:100. The metallurgical catalyst precursor composition comprises cobalt oxide crystalline particles dispersed in a mixture of antimony and tin compounds, with the total metal stoichiometry of cobalt:antimony and tin combined being 50:50, and most preferably the total metal stoichiometry of antimony:tin being up to 1:100, and optimally 1:200. These highly preferred embodiments of the metallurgical catalyst precursor composition may further comprise cobalt oxide crystalline particles consisting essentially of the preferred embodiments of cobalt oxide crystalline particles described herein above, in particular crystalline cobalt oxide having the formula Co3O4, and more preferably such crystalline particles may consist essentially of ruthenium at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particle, at least a portion of said ruthenium being present on the crystalline particle in the form of a surface decoration. In this latter embodiment, the cobalt oxide crystalline particles in the metallurgical catalyst precursor composition, in addition to the surface decoration, may further comprise crystalline regions in which ruthenium is incorporated within the crystal lattice of the cobalt oxide or forms a mixed metal oxide with cobalt, or both.
[0041] In an alternative embodiment of the method of the second aspect, the base composition is applied directly to the substrate prior to step (b), said applied metallurgical base composition advantageously having a total metal stoichiometry of Ru ≧0.3 (Sn+Ti) ≦0.7 The present invention relates to a method for producing a base composition comprising the steps of: (a) providing a ruthenium content of 0.3 or more atomic percent of the ruthenium in the base composition; and (b) providing a ruthenium content of 0.3 or more atomic percent of the tin and titanium in the base composition. It is important in the present invention that the ruthenium content of the base composition applied is at or above a stoichiometric level relative to the tin and titanium present in the base composition (corresponding to 30 atomic percent). It has been found that the durability of the resulting structural base layer is significantly improved when the ruthenium in the composition is at or above this level when applied according to the method of the second aspect. In addition, the ruthenium promotes the overall conductivity of the base structural composition. In this regard, the composition applied prior to step (b) may have a total metal stoichiometry of Ru in the composition. 0.3 (Sn+Ti) 0.7 It is preferred that the ruthenium, tin, and titanium compounds be included in an amount that provides: This level of ruthenium is optimal for the applied base composition of this embodiment of the method of the present invention, and is believed to result in a particularly efficient and durable anode structure.
[0042] The presence of a combination of tin and titanium in addition to ruthenium in the base composition, when applied by the method of the second embodiment, results in the formation of a structural base composition having the desired morphology of agglomerated particles and the absence of mud cracking behavior seen in other compositions containing only ruthenium and titanium or only tin. In this regard, a minimum level of 30 atomic % ruthenium relative to tin and titanium in the applied base composition also leads to enhanced formation of a network of agglomerated particles in the resulting structural base composition morphology, and a lack of cracking behavior. The presence of tin in the applied base composition in combination with ruthenium and titanium also contributes significantly to increasing the long term durability of anodes prepared according to the second embodiment, resulting in increased mechanical adhesion of the composite metallurgical layer to the anode substrate. To optimize these benefits, it is preferred that tin and titanium are present in approximately equal amounts in the applied base composition. Thus, most preferably, the applied base composition prior to step (b) has a total metal stoichiometry of Ru in this embodiment. 0.3 Sn 0.35 Ti 0.35 The present invention includes compounds of ruthenium, tin, and titanium in amounts providing
[0043] In the above embodiment of the second aspect, in addition to the essential compounds of ruthenium, tin, and titanium, trace amounts of other metal compounds may be present, but it is preferred that the base composition consists essentially of compounds of ruthenium, tin, and titanium, and the base composition preferably has a total metal stoichiometry of 100% to 150% by weight. 0.3 (Sn+Ti) 0.7 , most preferably with a total metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 More preferably, the catalyst comprises compounds of ruthenium, tin, and titanium in amounts providing: The metallurgical catalyst precursor composition for use in the method of the first aspect, and the structural base composition, if used, can each be prepared from compounds known in the art for the purpose of metal oxide catalyst preparation and mixed together in the appropriate ratio in the presence of a process solvent in accordance with the teachings of the present invention. Such compounds can include related metal oxide compounds, allowing for better mixing or suspension, and where practical, typically other compounds are used that will be oxidized under the subsequent heat treatment of the method to produce the desired metal oxide in situ. Thus, in the method of the second aspect, the ruthenium, tin and titanium compounds present in the applied composition each comprise compounds other than oxide compounds, and the heated application in the method, followed by drying and heat treating, preferably thermally decomposes these compounds into one or more of the respective metal oxide or mixed metal oxide compounds within the metallurgical layer of the final anode structure.
[0044] In this regard, the ruthenium, tin and titanium compounds present in any base composition preferably comprise, and more preferably consist of, their respective halide compounds and / or complexes with acetylacetone, the tin and antimony compounds in the metallurgical catalyst precursor composition preferably comprise, and more preferably consist of, their respective halide compounds, and ruthenium, when present, preferably comprises, and more preferably consists of, one or more of the corresponding halide compounds or complexes with acetylacetone. Such compounds provide suitable dispersion of the metals in the compositions used in the process, which are then converted to their respective oxides under the conditions of the process of the invention to give rise to the desired anode of the first aspect of the invention. The starting composition of the present method may further comprise other metal compounds that provide additional benefits to the resulting anode, as detailed in the first aspect. Thus, the starting composition may further comprise at least one palladium compound, preferably in an amount to provide a total palladium content of at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition. Preferably, the starting catalyst precursor composition further comprises at least one palladium compound, preferably in an amount to provide a total palladium content of at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition.
[0045] The catalyst precursor composition may further comprise at least one copper compound, or at least one aluminum compound, or at least one nickel compound, or more than one of the above, in an amount to provide composition (iii) with a total copper content of up to 10 atomic %, preferably up to 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of up to 30 atomic %, preferably up to 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of up to 15 atomic %, preferably up to 10 atomic %, based on the total metal atomic content of the composition, or more than one of the above, respectively. At least one of the starting process compositions may further comprise at least one iridium compound in an amount providing a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively, based on the total metal atomic content of the composition. Such additional metallic species may be introduced via compounds thereof that are conventionally used in the art for inclusion in metallurgical coatings. In a further preferred embodiment, the catalyst precursor composition does not contain any titanium compounds, and the process of the second aspect results in a titanium-free catalyst composition having the attendant advantages described herein above. In the method of the present invention, the conductive solid substrate consists essentially of a valve metal, preferably titanium, as detailed in the first aspect of the present invention. In the process of the present invention, the metallurgical catalyst precursor composition applied in step (b), and any underlying metallurgical interlayers, if present, may be applied sequentially by coating techniques known in the art, such as brush, roller, or drawdown application, spray coating by means such as electrospray or pressure spray, dip coating, and curtain coating, in which case thicker coatings may be applied, if desired, by coating techniques that include multiple passes over the underlying structure. Preferably, each metallurgical composition is applied sequentially by brush coating in one or more passes over the underlying structure, or by spray coating in one or more passes over the underlying structure, although other conventional techniques can also be used to apply one or more of the metallurgical compositions.
[0046] Third aspect of the present invention (electrochlorination system) In a third aspect, the present invention provides an electrochlorination system comprising an electrolytic anode structure obtainable by the method of the first aspect or of the second aspect, as described above.
[0047] Fourth aspect of the present invention (electrolysis method) In a fourth aspect, the present invention provides an electrolysis method for catalytically generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolysis cell comprising an electrolysis anode structure obtainable by the method of the first aspect or of the second aspect, at which chlorine gas is generated from the aqueous solution at the anode. In a preferred embodiment of the electrolysis process embodiment, the chlorine gas generated by the process is used as a biocide to disinfect water, more particularly, ballast water, or industrial wastewater, or municipal or domestic water, such as recreational water for swimming pools and domestic drinking water. In an alternative preferred embodiment, the process is a chlor-alkali process for producing and recovering chlorine.
[0048] Exemplary embodiments of the present invention 1. Preparation Example Preparation of Exemplary Starting Compositions for the Methods of the Invention 1.A Exemplary starting compositions for use in the present method were prepared from the following component compounds and liquids available in the art. Crystalline solid compounds: RuCl3.xH2O (commercially available, obtained from Sigma-Aldrich), SnCl4.5H2O (commercially available, obtained from Sigma-Aldrich), SbCl3 (commercially available, obtained from Sigma-Aldrich), PdCl2 (commercially available, obtained from Alfa Aesar), Ru(acac)3 (commercially available, obtained from Sigma-Aldrich; "acac" stands for acetylacetone), and Crystalline cobalt oxide particles having the chemical formula Co3O4, synthesized as follows: liquid: 2-propanol (also called isopropanol, commercially available and obtained from Alfa Aesar); Deionized water, TiCl3 solution (TiCl3 is commercially available and was obtained from Sigma-Aldrich and dissolved to a 12% solution in aqueous hydrochloric acid).
[0049] 1.B Preparation of the Base Interlayer Composition of the Present Method A total metal stoichiometry of Ru for use in the present method to form the structural base composition of a composite metallurgical layer. 0.3 Sn 0.35 Ti 0.35 A preferred base interlayer composition consisting essentially of a compound of ruthenium, tin, and titanium having the formula: was prepared according to the following sequence. In a 70 mL vial, add RuCl3.xHO (207.6 mg; 1 mmol) and SnCl 4.5H2O (409.4 mg; 1.17 mmol) was added. The solid material was dissolved in 2-propanol (17 ml) by vortexing until no metal precursor precipitated on standing. 1.5 mL of TiCl3 solution (12% TiCl3 in hydrochloric acid solution, 1.17 mmol) was added dropwise to the resulting solution with mechanical stirring at 1,000 rpm. Additionally, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours under ambient conditions with mechanical stirring at 1,000 rpm to produce a base composition for use in an alternative embodiment of the method of the present invention.
[0050] 1.C Preparation of Further Interlayer Compositions of the Present Method A composition consisting essentially of ruthenium dioxide for use in the present method to complement the optional intermediate layer was prepared according to the following sequence. A solvent was prepared by mixing 2-propanol (38.7 ml) and deionized water (7.8 ml). 15.5 ml of the prepared solvent was then placed in a 70 ml vial, to which 115.8 mg (0.29 mmol) of Ru(acac)3 and an additional 2 ml of IPA were added. The as-prepared solution was then sonicated for 20 minutes to produce an intermediate layer composition for use in the method of the present invention.
[0051] 1.D Preparation of the Metallurgical Catalyst Precursor Composition of the Present Method A preferred catalyst precursor composition consisting essentially of crystalline particles of cobalt oxide for use in the present process as a composition to form the composite metallurgical layer catalyst composition was prepared according to the following sequence. a) Synthesis of Co3O4 crystalline particles Co(NO3)26H2O (170 g, 0.584 mol) was dissolved in ethanol (99.9%, 510 ml) in a beaker at room temperature. To this mixture, 1-heptanol (510 ml) was added and the mixture was stirred for 5 minutes. The mixture was transferred to a pressure reactor and heated at 160°C for 7 hours. The resulting mixture was left for 16 hours to cool to room temperature and precipitate the solid product. The resulting supernatant was decanted and the resulting solid product was washed three times with isopropyl alcohol (100 ml). Between each wash, the product was mixed well and then centrifuged at 8500 rpm for 1 hour. In each case, the supernatant was decanted off. Isopropyl alcohol (IPA) was added to a solids content of 12% by weight (the amount of IPA added was calculated from the density of the resulting solution after mixing). The resulting mixture was dispersed using a ball mill with 0.5 mm ZrO2 beads at room temperature for 2 hours at 2000 rpm to obtain a 12 wt% Co3O4 nanoparticle solution. The size of the Co3O4 crystalline particles synthesized above was determined by directly measuring the diameter on transmission electron micrograph images, and was found to be in the range of 3 nm to 7 nm, with a median diameter of 5 nm.
[0052] b) Preparation of Metallurgical Catalyst Precursor Composition A solvent was prepared by mixing 2-propanol (38.7 ml) and deionized water (7.8 ml). In this solvent, SbCl3 (44.7 mg; 0.20 mmol) was dissolved by vortexing. 5 ml of this as-prepared solution was then diluted with an additional 45 ml of the solvent mixture to form a first "antimony solution". 15.5 ml of this antimony solution was then mixed with SnCl4.5H2O (457.8 mg, 1.31 mmol) by vortexing to form an "antimony-tin solution". PdCl2 (4.8 mg; 0.027 mmol) was placed in a 70 ml vial, and then the prepared antimony-tin solution was poured into the vial. In addition, 1 ml of the Co3O4 crystalline particle solution (0.438 mmol) prepared in a) above and 1 ml of 2-propanol were each added to the solution. Finally, the mixture was sonicated for 20 minutes to produce a precursor composition for use in the method of the present invention. This composition comprises Co3O4 crystalline particles with palladium incorporated at a level of 1 atomic % in a solution of antimony and tin compounds, with an antimony:tin molar ratio of 1:247 and a total metal stoichiometry of cobalt:antimony and tin combined of 50:50.
[0053] Preparation of the catalytic anode of the present invention by the method of the present invention Example 1: Catalyst precursor composition applied directly to an anode substrate A titanium mesh was prepared as an anode substrate, which was heated to a temperature of 100° C. using a heating plate after cleaning. At this temperature, the above prepared composition 1D was applied to the heated substrate surface by brush coating. The resulting coated sample was held at 100° C. for 1 minute, the substrate was turned over, the back side was coated again, and the substrate was held at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven and left there for 5 minutes. The coated sample was then returned to the 100° C. hot plate and the coating and heat treatment steps were repeated. This brush coating of the substrate surface with this composition was repeated four more times, resulting in a total of five brush passes over the surface to be coated.
[0054] Example 2: An intermediate layer composition coated directly onto an anode substrate and overlaid with a catalyst precursor composition An anode according to this embodiment of the first aspect of the invention was prepared according to the method of the second aspect of the invention as follows. A titanium mesh was prepared as an anode substrate, which was heated to a temperature of 100° C. using a heating plate after cleaning. At this temperature, the base composition of 1.B prepared above was applied to the heated substrate surface by brush coating. The resulting coated sample was held at 100° C. for 1 minute, the substrate was turned over, the back side was coated again, and the substrate was held at 100° C. for 1 minute. The coated sample was then transferred to a 500° C. oven and left there for 5 minutes. The coated sample was then returned to the 100° C. hot plate and the coating and heat treatment steps were repeated. This brush coating of the substrate surface with this composition was repeated four more times, resulting in a total of five brush passes over the surface to be coated. The resulting structure was then further brush-coated with the intermediate layer composition 1.C prepared above in the same manner as described above, for a total of 5 brush passes over the surface. The resulting structure was then further brush-coated with the catalyst precursor composition 1D prepared above, for a total of 10 brush passes over the surface. After these coating steps, the resulting coated structure was dried at the same temperature. The dried resultant structure was then subjected to a final heat treatment in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.
[0055] Example 3: An anode substrate already directly coated with a conventional dimensionally stable anode composition and overlaid with a catalyst precursor composition A commercially available anode structure, previously coated with a conventional dimensionally stable anode composition, was then coated with a ruthenium oxide interlayer prepared according to Section 1.C above, and then with a metallurgical catalyst precursor composition prepared according to Section 1.D above, following application steps similar to those used in Example 2 above. The result was an anode structure having a multi-layer coating in which the base layer was a dimensionally stable anode composition, the intermediate layer was ruthenium oxide, and the surface layer was a metallurgical catalyst layer according to the present invention.
[0056] 2. Performance examples The performance and advantages of the anode of the present invention were demonstrated using the following experimental techniques. Chlorine Evolution Reaction (CER) Efficiency Test: The faradaic efficiency of the electrolytic cell provides an important indicator of the efficiency of the catalytic anode for the CER reaction. An electrolytic cell using a counter electrode (cathode) and a working electrode (anode according to the invention) was set up as follows. 5×15cm 2 The Ti mesh counter electrode was etched in 2.0 M sulfuric acid at 60° C. for 1 h until the etching solution turned pale purple. The etched Ti mesh was then sonicated several times in 95% pure ethanol for 10 min. The rinsed Ti mesh was blown dry with nitrogen gas. The dried counter electrode was masked with silicon tape and electroplating tape to obtain a 5×5 cm 2 left the area.
[0057] Anodes prepared according to the present invention were also masked with silicone tape and electroplating tape to form 1×5 cm 2 Masking the electrodes helped to concentrate the current in the limited areas of the electrodes exposed to the electrolyte, thus increasing the current density and accelerating the test. The electrolysis cell was assembled by attaching a masked counter electrode to one side of an electrode frame and a working electrode to the other side of the frame, with a portion of the frame at the bottom end of both electrodes maintaining a 5 mm gap between the electrodes. The test cell was constructed and operated under the following conditions. a) 500 ml of 20 mM NaCl solution was poured into a 500 ml beaker. The electrode cell assembled above was placed in the beaker, and two electric wires were connected to the working electrode and the counter electrode, respectively. b) The solution was stirred at 300 rpm using a magnetic stir bar. The attached potentiostat was then switched to 40 mA / cm for 1 min under 300 rpm stirring conditions. 2 The device was operated in chronopotentiometry mode at 400 rpm. c) After 1 minute of operation, the active chlorine concentration was measured and compared with the theoretical concentration obtained from the initial chloride ion concentration to determine the faradaic efficiency (FE) of the cell incorporating the working electrode (anode of the present invention).
[0058] Active chlorine concentration was measured by one of two interchangeable methods described below. Measurement of active chlorine concentration by DPD colorimetry In this method, the DPD vial was washed with DI water until initial testing confirmed that no residual active chlorine was present in the test vial. After the electrolysis cell was operated for 1 minute, the solution was stirred at 600 rpm for 1 minute to create a completely homogenous test solution. 1 ml of this well-mixed solution was then diluted 1 in 10 with 20 mM NaCl solution in a DPD vial to bring the test solution volume to 10 ml. DPD reagent was then added to the DPD vial and the vial was vortexed for 10 seconds. The active chlorine concentration was then measured with a DPD pocket colorimeter and the amount of active chlorine produced was divided by the theoretical active chlorine production to calculate the faradaic efficiency (FE).
[0059] Measurement of active chlorine concentration by iodometric titration After the electrolysis cell was operated for 1 minute, the solution was stirred at 300 rpm to produce a homogenous solution. 1.6 g of KI (potassium iodide) was then added to the beaker containing the solution. After the KI was added, the solution turned a light yellow color. After 4 ml of glacial acetic acid was added to the solution, the solution turned a light orange color. After 4 ml of starch solution was added to the beaker, the solution turned a deep blue color. The deep blue solution was then titrated with 0.02 N sodium thiosulfate until the solution became colorless, and the amount of active chlorine produced was estimated from the titration amount of sodium thiosulfate added. Again, the faradaic efficiency was calculated by dividing the amount of active chlorine produced by the theoretical active chlorine production.
[0060] Chlorine Evolution Reaction (CER) Life Test: The faradaic efficiency of the electrolytic cell, measured periodically over long-term testing, provides an important demonstration of the life of the catalytic anode and therefore of the durability of the anode for the CER reaction. A rapid increase in FE is an indication of anode degradation and, in the case of durability for CER, indicates that a limit is being reached. An electrolytic cell with counter and working electrodes was constructed as described above. For purposes of accelerating the test, the working electrode (anode) was placed 1 cm 2 The area was masked to concentrate the current density. Masking was performed by applying a silicon tape and then applying an electroplating tape on top of it. In addition, before connecting, the top of the working electrode was polished back to the metal substrate. a) 1 liter of 0.6M NaCl solution was poured into a beaker surrounded by a cooling jacket, and the test solution was maintained at 15° C. After allowing the temperature to stabilize for 1 hour, the electrode cell assembled above was placed in the beaker, and two wires were connected to the working electrode and counter electrode, respectively. b) The solution was stirred at 300 rpm using a magnetic stir bar, and the attached potentiostat was then operated in chronopotentiometry mode. c) During operation, the cell potential was repeatedly measured and plotted over time to report the CER potential over the life test duration and to identify the degradation point where the potential increased rapidly beyond the useful life of the anode.
[0061] Mechanical Adhesion Test The mechanical adhesion of the metallurgical surface layer of the anode was evaluated by the following method: A piece of 3M electroplating tape, prepared as detailed above, was placed over the unmasked portion of the working electrode (the anode being tested). Light pressure was applied with a pipette tip to loosen the tape and allow it to adhere firmly to the coated electrode surface. The tape was then removed and the extent of metallurgical coating residue remaining on the adhesive surface of the removed tape was visually evaluated as a measure of the coating adhesion strength to the electrode substrate. More residue on the removed tape indicates poorer residual adhesion to the substrate. Acid Stability Test A 5% by weight hydrochloric acid solution was prepared by diluting concentrated hydrochloric acid with deionized water to the required amount. The anode to be tested was cut to a size of 2 cm x 1 cm and placed in a 10 ml vial, to which 5 ml of 5% hydrochloric acid solution was added so that the anode sample was completely immersed. The color of the sample and the acid solution were observed over time.
[0062] 2.1 Performance of the catalyst composition of the present invention The importance of catalyst chemistry to performance is discussed below. 2.1(a) Inclusion of a tin and antimony oxide matrix in the catalyst composition The advantage of having cobalt, tin, and antimony present in the specified stoichiometric ratios is illustrated in Figures 3 and 4. Similar anodes were prepared following the example of embodiment 1 in Section 1 above, but using catalyst precursor compositions with different tin and antimony contents, as shown in the figures. In each case, life tests were performed and (over)potentials were compared over time. As shown in Figure 3, the total metal stoichiometry of cobalt:antimony plus tin in the catalyst precursor composition affects the life of the anode. Anode structures fabricated from catalyst precursor compositions having a molar ratio in the range of 20:80 to 80:20, preferably 50:50, show significant improvement in durability in terms of maintaining a low potential over a longer operating life. In this regard, the 50:50 molar ratio provided the best performance. As Figure 4 shows, for a similar anode prepared according to the example of embodiment 2 in Section 1 above, varying the antimony and tin compounds in amounts that provide the catalyst precursor composition with a total metal stoichiometry of antimony:tin up to 1:20 shows a lifetime advantage over anodes having ratios greater than 1:10. In addition, in Figure 5, the CER efficiency, as measured by faradaic efficiency (FE) using the method detailed earlier herein, shows increasing advantage with ratios of 1:20, 1:50, 1:100, and 1:200, the latter being the most highly effective catalyst precursor composition and resulting in the most efficient anode.
[0063] 2.1(b) Inclusion of Palladium Oxide in the Catalyst Composition In further experiments, the anode was directly coated with a catalyst composition according to the present invention comprising cobalt oxide particles, ruthenium oxide, and tin oxide and antimony oxide, and the effect of introducing palladium as an additional component was evaluated. The results are shown in the table below, and demonstrate that the preferred inclusion of a small amount of palladium in the catalyst composition provides improved efficiency. [Table 1] (Exposed electrode area (5cm 2 ), NaCl concentration is 1.17g / L)
[0064] 2.1(c) Improvements provided by catalyst compositions on anode structures having dimensionally stable anode interlayers. CER efficiency and CER life tests were performed on a conventional anode coated with a dimensionally stable anode composition compared to an improved anode of the same anode coated with a ruthenium oxide intermediate layer followed by a metallurgical catalyst composition according to embodiment 3 of section 1 above (measured by SEM / EDX at 20 kV accelerating voltage, Ru: 15.7, Ti: 11.93, Ir: 1.51 at%). The results are shown in the table below. [Table 2]
[0065] As these results show, the addition of a cobalt-based metallurgical catalyst layer and a ruthenium oxide intermediate layer to form an anode of the present invention increased the CER efficiency by 16.1% over the conventional DSA catalyst layer alone, and the life span of the anode of the present invention was increased by 33% over the conventional anode.
Claims
1. A catalytic anode structure for use in an electrochlorination system comprising an electrically conductive solid substrate having overlaid on its surface facing an electrolyte a conductive metallurgical catalyst layer, the layer being comprised of a metal of chemical formula Co in a crystalline matrix of oxides of antimony and tin. 3 O 4 The cobalt oxide crystalline particles essentially consist of crystalline cobalt oxide having the cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the metallurgical catalytic layer, and the total metal stoichiometric ratio of cobalt:antimony and tin combined in the metallurgical catalytic layer is in the range of 2:1 to 9:1; Catalytic anode structure.
2. 2. The anode structure of claim 1, wherein the antimony and tin compounds are present in the metallurgical catalyst layer in amounts providing a total metal stoichiometry of antimony:tin in the range of 1:5 to 1:200, preferably in the range of 1:5 to 1:
100.
3. 3. The anode structure according to claim 1 or claim 2, wherein the metallurgical catalytic layer further comprises one or more precious metals or compounds thereof, preferably ruthenium or an oxide thereof.
4. 4. The anode structure of claim 3, wherein the cobalt oxide crystalline particles in the metallurgical catalyst layer consist essentially of ruthenium or an oxide thereof at a level of up to 5 atomic % ruthenium based on the total metal atomic content of the crystalline particles, and at least a portion of the ruthenium is present on the crystalline particles in the form of a surface decoration.
5. 5. The anode structure of claim 4, wherein the cobalt oxide crystalline particles in the metallurgical catalyst layer further include crystalline domains in which ruthenium is incorporated within the crystal lattice of the cobalt oxide, or forms a mixed metal oxide with cobalt, or both.
6. 6. The anode structure of claim 3, wherein the metallurgical catalytic layer comprises at least one palladium compound in an amount providing the metallurgical catalytic layer with a total palladium content of at most 7 atomic %, preferably at most 3 atomic %, of the total metal atomic content of the metallurgical catalytic layer.
7. The anode structure of any one of claims 3 to 6, wherein the metallurgical catalytic layer further comprises ruthenium oxide distributed throughout or substantially throughout the catalytic layer.
8. 8. The anode structure of claim 3, wherein the metallurgical catalytic layer further comprises iridium in the form of its oxide or other catalytically active species in an amount to provide a total iridium content of up to 15 atomic %, preferably up to 5 atomic %, of the total metal atomic content of the metallurgical catalytic layer.
9. An anode structure according to any one of claims 1 to 8, wherein the conductive solid substrate consists essentially of a valve metal, preferably titanium.
10. 10. The anode structure of any one of claims 1 to 9, wherein the metallurgical catalytic layer further comprises at least one copper compound in an amount to provide to the layer a total copper content of at most 10 atomic %, preferably at most 2 atomic %, of the metallurgical layer; or at least one aluminum compound in an amount to provide to the layer a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, of the metallurgical layer; or at least one nickel compound in an amount to provide to the layer a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, of the total metal atomic content of the metallurgical catalytic layer; or more than one of the above.
11. The anode structure of any one of claims 1 to 10, wherein the metallurgical catalyst layer does not include titanium or compounds thereof.
12. 12. An anode structure according to any one of claims 1 to 11, wherein the anode structure consists of a conductive solid substrate overlaid on its surface facing the electrolyte with a conductive metallurgical catalyst layer as defined in any one of claims 1 to 11, the catalyst layer being directly adjacent to the substrate.
13. 12. The anode structure of any one of claims 1 to 11, wherein the anode structure comprises an electrically conductive solid substrate overlaid on its surface facing the electrolyte with a metallurgical intermediate layer immediately adjacent to the substrate, the intermediate layer being overlaid with an electrically conductive metallurgical catalyst layer as defined in any one of claims 1 to 11.
14. 14. The anode structure of claim 13, wherein the intermediate layer is a dimensionally stable anode composition.
15. 15. The anode structure of claim 13 or claim 14, wherein the intermediate layer comprises titanium or one or more compounds thereof, or tantalum or one or more compounds thereof, or both.
16. Anode structure according to any one of claims 13 to 15, wherein said intermediate layer comprises ruthenium or one or more compounds thereof, and preferably further comprises titanium or one or more compounds thereof.
17. The anode structure according to any one of claims 13 to 16, wherein the intermediate layer comprises iridium or one or more compounds thereof.
18. An anode structure according to any one of claims 13 to 17, wherein the titanium, tantalum, ruthenium or iridium compound, if present, comprises, and preferably consists of, an oxide compound.
19. A method for preparing a catalytic anode structure for use in an electrochlorination system comprising the following sequence of steps: a) providing or obtaining a conductive solid substrate; b) providing on the surface of said substrate facing the electrolyte a compound of formula Co dispersed in a mixture of antimony and tin compounds; 3 O 4 wherein the cobalt oxide is present in an amount of at least 12.5 atomic % of the total metal atomic content of the composition, and wherein the total metal stoichiometric ratio of cobalt:antimony and tin combined in the composition is in the range of 20:80 to 80:
20. Including, the process solvent used to apply the metallurgical catalyst precursor composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:20 to 95:5; The resulting structure is then dried and then heat treated at a temperature of at least 450°C. method.
20. 20. The method of claim 19, wherein the substrate (a) is heated to a temperature in the range of 55 to 200° C. during step (b), and the resulting structure is then dried at a temperature in the same range.
21. 21. The method of claim 20, wherein the substrate (a) is heated to a temperature of 100° C. during step (b), and the resulting structure is then dried at that temperature.
22. The method according to any one of claims 19 to 21, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.
23. The method according to any one of claims 19 to 22, wherein the heat treatment temperature is 500°C.
24. 24. The method of any one of claims 19 to 23, wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio range of 80:
15.
25. 25. The method of any one of claims 19 to 24, wherein each metallurgical composition applied in step (b) is applied in sequence by brush coating in one or more passes over the underlying structure.
26. 26. The method of any one of claims 19 to 25, wherein each metallurgical composition applied in step (b) is applied sequentially by spray coating in one or more passes over the underlying structure.
27. 27. The method of any one of claims 19 to 26, wherein the cobalt oxide crystalline particles in the metallurgical catalyst precursor composition further consist essentially of ruthenium at a level of up to 5 atomic % ruthenium, based on the total metal atomic content of the crystalline particles, at least a portion of the ruthenium being present on the crystalline particles in the form of a surface decoration.
28. 28. The method of claim 27, wherein the cobalt oxide crystalline particles in the metallurgical catalyst precursor composition further comprise crystalline domains in which some ruthenium is incorporated within a crystal lattice of the cobalt oxide, or some ruthenium forms a mixed metal oxide with cobalt, or both.
29. 29. The method of any one of claims 19 to 28, wherein the antimony and tin compounds are present in the metallurgical catalyst precursor composition in amounts to provide a total metal stoichiometric ratio of antimony:tin of up to 1:10, preferably up to 1:20, and most preferably 1:
200.
30. 30. The method of any one of claims 19 to 29, wherein the metallurgical catalyst precursor composition further comprises at least one palladium compound in an amount to provide the composition with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the composition.
31. 31. The method of any one of claims 19 to 30, wherein the tin and antimony compounds in the metallurgical catalyst precursor composition each comprise a compound other than an oxide compound, and the heated application in step (b) followed by drying and heat treating thermally decomposes these compounds into one or more of the respective metal oxide or mixed metal oxide compounds within the metallurgical catalyst layer of the final anode structure.
32. 32. The method of claim 31 , wherein the tin and antimony compounds, if present, initially comprise, and preferably consist of, their respective halide or sulfate compounds.
33. 33. The method of any one of claims 19 to 32, wherein the metallurgical catalyst precursor composition further comprises at least one copper compound, or at least one aluminum compound, or at least one nickel compound, or more than one of the above, in an amount to provide the composition with a total copper content of up to 10 atomic %, preferably up to 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of up to 30 atomic %, preferably up to 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of up to 15 atomic %, preferably up to 10 atomic %, based on the total metal atomic content of the composition, or more than one of the above, respectively.
34. 35. The method of any one of claims 19 to 34, wherein the metallurgical catalyst precursor composition further comprises at least one iridium compound in an amount providing a total iridium content of up to 15 atomic %, preferably up to 10 atomic %, respectively, based on the total metal atomic content of the composition.
35. A method according to any one of claims 19 to 34, wherein the conductive solid substrate consists essentially of a valve metal, preferably titanium.
36. The method of any one of claims 19 to 35, wherein in step (b), the metallurgical catalyst precursor composition is applied directly to an electrolyte-facing surface of the substrate.
37. 37. The method of any one of claims 19 to 36, wherein prior to step (b), a metallurgical base composition is applied directly to an electrolyte-facing surface of the substrate to form a metallurgical interlayer immediately adjacent the substrate surface, and in step (b), the metallurgical catalyst precursor composition is applied to an outer surface of the metallurgical interlayer.
38. An electrochlorination system comprising an electrolytic anode structure according to any one of claims 1 to 18 or obtainable by the method according to any one of claims 19 to 37.
39. 38. An electrolytic process for generating chlorine gas from an aqueous solution containing chloride ions, comprising the step of passing an electric current through said solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method according to any one of claims 1 to 18 or any one of claims 19 to 37, wherein chlorine gas is generated from said aqueous solution at said anode.
40. 40. The electrolysis process of claim 39, wherein chlorine gas evolution from the aqueous solution is facilitated by catalytic action of the metallurgical catalyst layer overlying a surface of the anode.
41. 41. The electrolytic process according to claim 39 or 40, wherein the chlorine gas generated by the process is used as a biocide for disinfecting water.
42. 42. The electrolysis method according to claim 41, wherein the chlorine gas is used to disinfect ballast water or industrial wastewater.
43. 41. An electrolytic process according to claim 39 or 40, wherein the process is a chlor-alkali process for the production and recovery of chlorine.